Death After Life or Life After Death? - Sim, David C. (Scrinium, 2015)
The early Church Fathers accepted the notion of an intermediate state, the existence of the soul following death until its reunification with the body at the time of the final resurrection. This view is common in the modern Christian world, but it has been challenged as being unbiblical. This study reflects upon this question. Does the New Testament speak exclusively of death after life, complete lifelessness until the day of resurrection, or does it also contain the notion of life after life or immediate post-mortem existence? It will be argued that, while the doctrine of future resurrection is the most common Christian view, it was not the only one present in the Christian canon. There are hints, especially in the Gospel of Luke and the Revelation of John, that people do indeed live again immediately after death, although the doctrine of resurrection is also present. These two ideas are never coherently related to one another in the New Testament and it was the Church Fathers who first sought to systematise them.